2016
DOI: 10.1007/s00253-016-7493-9
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biocatalytic characterization of 17 novel halohydrin dehalogenases

Abstract: Halohydrin dehalogenases are rare but catalytically remarkable enzymes since they are able to form novel C-C, C-O, C-N, or C-S bonds. Very recently, a motif-based sequence database mining approach resulted in the identification of 37 novel halohydrin dehalogenase enzymes, many of them exhibiting only low sequence similarity to previously known halohydrin dehalogenases. In an attempt to explore the biocatalytic potential of these newly identified enzymes, 17 representatives from all six phylogenetic subtypes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 31 publications
5
66
0
2
Order By: Relevance
“…HheG from Ilumatobacter coccineus was active on all five epoxide substrates yielding highest conversion for substrates 1 , 3 , 4 and 5 among all tested HHDHs. Significant conversion of 5 by HheG was unexpected as the enzyme was shown to exhibit only very little activity on styrene oxide . For HheA2 and HheB2, hardly any product formation in the conversion of the tested vicinally di‐substituted epoxides was observed, which is in agreement with previous findings …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…HheG from Ilumatobacter coccineus was active on all five epoxide substrates yielding highest conversion for substrates 1 , 3 , 4 and 5 among all tested HHDHs. Significant conversion of 5 by HheG was unexpected as the enzyme was shown to exhibit only very little activity on styrene oxide . For HheA2 and HheB2, hardly any product formation in the conversion of the tested vicinally di‐substituted epoxides was observed, which is in agreement with previous findings …”
Section: Resultssupporting
confidence: 91%
“…This is also supported by calculations of the active site volume of HheG, which was found to be 2.7 times larger than the calculated active site volume of HheC . On the other hand, epoxide substrates with much bulkier substituents on both carbon atoms of the epoxide ring are likely not accepted by HheG as it was previously shown that trans ‐stilbene oxide was not converted by HheG or other tested HHDHs …”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations